FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - ANWAR HARSONO (Jurnal Bisnis dan Akuntansi, 2018)
The objective of the research is to obtain empirical evidence on the effect of independent variables of firm size, cash, capital expenditure, dividend policy, debt policy, return on asset, managerial ownership, and institutional ownership to firm value.The population used in this study are non-financial companies listed on the Indonesia Stock Exchange from 2013-2016. Intake of data in this research using purposive sampling method. There are 54 non-financial companies that fit the criteria and were selected as the final sample. This study uses multiple regression analysis to test the hypothesis. The value of firms in this study was measured using Tobins'Q.The empirical results of this study indicate that the variables independent debt policy and return on assets have an influence on firm value, while the variables of firm size, cash, capital expenditure, dividend policy, managerial ownership, and institutional ownership have no effect on firm value.